2010
DOI: 10.1007/s12289-010-0809-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental development of RSM techniques for surface quality prediction in metal cutting applications

Abstract: The aim of this work is to analyze the influence of cutting conditions on surface roughness with slot end milling on AL7075-T6. The considered parameters are: cutting speed, feed, depth of cutting and mill radial engage. Response surface models based on experimental data obtained with physical tests have been developed, the authors have performed a consistent set of experimental tests based on design points selected within the four-dimensional design space. Each test has been repeated 3 times to ensure the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…If simple geometrical equations exist to estimate the mean surface roughness (R a ) and mean surface roughness depth (R z ), being able to predict them over a wide range of cutting parameters requires some other approaches. Response Surface Methodology (RSM) (Del Prete et al 2010a) and ANOVA (Saffioti et al 2021b) were commonly applied to generate empirical models and assess the most influential parameters. In broaching, Makarov et al (2008) and Arrieta et al (2017) showed that surface roughness was also highly dependent on the microstructure of the material especially due to the small uncut chip thickness compared to the grain size.…”
Section: Prediction Of Surface Integritymentioning
confidence: 99%
“…If simple geometrical equations exist to estimate the mean surface roughness (R a ) and mean surface roughness depth (R z ), being able to predict them over a wide range of cutting parameters requires some other approaches. Response Surface Methodology (RSM) (Del Prete et al 2010a) and ANOVA (Saffioti et al 2021b) were commonly applied to generate empirical models and assess the most influential parameters. In broaching, Makarov et al (2008) and Arrieta et al (2017) showed that surface roughness was also highly dependent on the microstructure of the material especially due to the small uncut chip thickness compared to the grain size.…”
Section: Prediction Of Surface Integritymentioning
confidence: 99%
“…[10]. The roughness on worked surfaces have been detected with Mahr's Perthometer Concept 6.5 profilometer.…”
Section: Experimental Equipmentsmentioning
confidence: 99%